2024
DOI: 10.1177/08980101241237903
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Rehabilitation in Action: A Data-Driven Analysis of the Impact on Quality of Life among Individuals with Psychoactive Substance Abuse

Shella Febrita Puteri Utomo,
Inggriane Puspita Dewi,
Nordianna Seman
et al.

Abstract: Background: Psychoactive substance abuse can affect biological, psychological, social, and spiritual aspects, as well as the users’ quality of life, and obliged to carry out medical and social rehabilitation. Purpose: The purpose of the study was to identify the effect of holistic rehabilitation programs on quality of life among drug abusers. Methods: Quasi-experimental with time series design. The sample of this study amounted to 54 people, taken by G-power, all participants who will take part in the rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…SEFT is recommended as a nurse-initiated intervention in the management of advanced breast cancer pain, and it is also supported by Komariah et al (2023) research on interventions with an Islamic approach, specifically Islamic mindfulnessbased caring (IMC), which affects fatigue levels in breast cancer patients. Furthermore, therapies with a holistic approach were evaluated for effectiveness in research (Utomo et al, 2024); the findings revealed that a holistic recovery program improves the quality of life of drug abusers. Several research has investigated aspects of environmental change associated with the COVID-19 pandemic, including ailments like hypertension (Kristinawati et al, 2023) and psychological disorders (Diannita et al, 2023;Sriati et al, 2023).…”
mentioning
confidence: 99%
“…SEFT is recommended as a nurse-initiated intervention in the management of advanced breast cancer pain, and it is also supported by Komariah et al (2023) research on interventions with an Islamic approach, specifically Islamic mindfulnessbased caring (IMC), which affects fatigue levels in breast cancer patients. Furthermore, therapies with a holistic approach were evaluated for effectiveness in research (Utomo et al, 2024); the findings revealed that a holistic recovery program improves the quality of life of drug abusers. Several research has investigated aspects of environmental change associated with the COVID-19 pandemic, including ailments like hypertension (Kristinawati et al, 2023) and psychological disorders (Diannita et al, 2023;Sriati et al, 2023).…”
mentioning
confidence: 99%